Evidence for superconductivity and a pseudogap in the new magnetic compound PrAg6In6 - Dmitriev, V.M.; Rybaltchenko, L.F.; Wyder, P.; Jansen, A.G.M.; Prentslau, N.N.; Suski, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Direct evidence for superconductivity in the new magnetic compound PrAg6In6 is revealed for the first time. The distinct Andreev-reflection current is observed in metallic point contacts (PC) based on this compound. The data obtained provide reason enough to suggest that the rise of superconductivitystrongly depends on the local magnetic order varying over the sample volume. The triangular-shaped PC spectra (dV/dI(V)) in the vicinity of the zero-bias voltage suggest an unconventionaltype of superconducting pairing. As follows from the temperature and magnetic field dependences of the PC spectra, the superconducting energy gap structure transforms into the pseudogap one as the temperature or the magnetic field increases.